Barcode Scanner using Android Platform - Ivan Michael Siregar; Ryan Salvator (President University, 2016)
In this 21st century era, technology become much more effective and efficient, less time consuming, less human resource needed, less expense, etc. During the development of technology, everything turned out to be easier. The idea of using barcode are spreading with its barcode scanner with limited functions (ex : the distance limited with its cord), and we must buy the specific device to use it; not to mention that some scanner provide scanning a bar lines only, not QR-Code one. In this paper, the barcode scanner will be installed in the smart device that is using the android operating system with its extended function such as text to speech implemented, signal strength display, and ping and connect function. The purpose of this scanner is to scan a data and send the decoded one to the server that has been set up. The Scanner itself can look at the main database if we are far away from the server. The server itself functions just like in medicine shops; it has the medicine database with its supplier and log history. Also it has two functions that only the admin can access it, confirming and deleting data. Confirming data will input the item that has already scanned to the main database, while deleting data will reduce the amount of item in the database. The server itself will be put on the internet so it can be accessed everywhere if there is an internet connection. This research aims to overcome its limitation, the scanner will be used in a smart device that modified to fulfil its requirement and make it become more effective and efficient.